2012
DOI: 10.1001/archgenpsychiatry.2011.2277
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversities and First Onset of Psychiatric Disorders in a National Sample of US Adolescents

Abstract: Context Although childhood adversities (CAs) are known to be highly co-occurring, most research examines their associations with mental disorders one at a time. Recent evidence from adult studies suggests, though, that the associations of multiple CAs with mental disorders are non-additive, arguing for the importance of multivariate analysis of multiple CAs. No attempt has yet been made to carry out a similar kind of analysis among children or adolescents. Objective To examine the multivariate associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
672
4
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 791 publications
(723 citation statements)
references
References 65 publications
33
672
4
14
Order By: Relevance
“…Exposure to trauma is particularly detrimental when it occurs in childhood or adolescence, disrupting numerous aspects of development in cognitive, emotional, and social domains, leading to adverse mental health and educational outcomes (Cicchetti & Toth, 1995; Koenen, Moffit, Caspi, Taylor, & Purcell, 2003) with long-term consequences for learning and memory (Teicher, Anderson, & Polcari, 2012), emotional functioning (De Bellis et al, 1994; McCrory et al, 2011; McLaughlin & Hatzenbuehler, 2009; Pollak & Sinha, 2002; Pollak, Vardi, Putzer Bechner, & Curtin, 2005), social relationships, elevated risk of re-victimization (Cole & Putnam, 1992; DiLillo, 2001; Follette, Polusney, Bechtle, & Naugle, 1996), and mental disorders (Kilpatrick et al, 2003; McLaughlin et al, 2012, 2013). …”
Section: Public Health Impact Of Traumamentioning
confidence: 99%
“…Exposure to trauma is particularly detrimental when it occurs in childhood or adolescence, disrupting numerous aspects of development in cognitive, emotional, and social domains, leading to adverse mental health and educational outcomes (Cicchetti & Toth, 1995; Koenen, Moffit, Caspi, Taylor, & Purcell, 2003) with long-term consequences for learning and memory (Teicher, Anderson, & Polcari, 2012), emotional functioning (De Bellis et al, 1994; McCrory et al, 2011; McLaughlin & Hatzenbuehler, 2009; Pollak & Sinha, 2002; Pollak, Vardi, Putzer Bechner, & Curtin, 2005), social relationships, elevated risk of re-victimization (Cole & Putnam, 1992; DiLillo, 2001; Follette, Polusney, Bechtle, & Naugle, 1996), and mental disorders (Kilpatrick et al, 2003; McLaughlin et al, 2012, 2013). …”
Section: Public Health Impact Of Traumamentioning
confidence: 99%
“…Several studies have shown that childhood physical abuse, sexual abuse, and witnessing family or community violence are factors that may lead to impaired mental health in adolescence Helweg-Larsen, Frederiksen, & Larsen, 2011;McLaughlin et al, 2012;Mills et al, 2013), as well as later in life Chapman et al, 2004;Franzese, Covey, Tucker, McCoy, & Menard, 2014;. Studies of childhood abuse in the Norwegian general population have reported a prevalence of physical abuse of 5-6% (both sexes) and of sexual abuse of 10-14% (girls) and 3-4% (boys) .…”
Section: B S T R a C Tmentioning
confidence: 99%
“…Structured psychiatric interviews are considered to be the most reliable method to estimate the prevalence of psychiatric diagnoses in a study population, yet the majority of previous studies are based on self-report questionnaires Helweg-Larsen et al, 2011;Peltonen, Ellonen, Larsen, & Helweg-Larsen, 2010) and conducted on general adult Green et al, 2010) or adolescent (McLaughlin et al, 2012) populations.…”
Section: B S T R a C Tmentioning
confidence: 99%
“…CM and AS have both consistently been implicated as risk factors for psychopathology, including anxiety disorders (Collishaw et al, 2007; Kessler, McLaughlin et al, 2010; McLaughlin et al, 2007, 2012). We have previously determined, in a sample of secondary school-attending adolescents, that CM is significantly and positively associated with anxiety-related temperamental traits such as AS and trait anxiety (Martin, Viljoen, Kidd, & Seedat, 2014).…”
Section: Introductionmentioning
confidence: 99%